2022
DOI: 10.3389/fmars.2022.895723
|View full text |Cite
|
Sign up to set email alerts
|

Rare earth element behaviour in seawater under the influence of organic matter cycling during a phytoplankton spring bloom – A mesocosm study

Abstract: Rare earth elements (REEs) are used as powerful proxies for a variety of oceanic processes. The understanding of their biogeochemical behaviour in the marine environment is therefore essential. While the influence of OM-cycling on REE patterns in seawater is considered as insignificant, it has been shown that algae and bacteria provide good sorption surfaces for REEs and that components of the dissolved OM pool are able to complex REEs, thus potentially altering their behaviour. To investigate the impact of bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…According to Neira et al [22], heavy REEs tend to remain in solution-forming complexes usually unavailable for organisms, while light REEs (such as Ce) are most likely to be assimilated by them, posing potential biological implications. In general, in seawater, the toxicity of Ce and Gd compounds may be influenced by the interaction of the metal cation (Ce 3+ or Gd 3+ ) with other conjugated anions (e.g., SO 4 2− or Cl − ) [23]. REE concentrations in the ocean generally decrease from surface waters to mid depths (ranging from 6 to 10 m), before increasing near the sea bottom [22,24], and according to Akagi et al [25], the diatoms' presence may be a major pathway of REE transport to deeper layers.…”
Section: Discussionmentioning
confidence: 99%
“…According to Neira et al [22], heavy REEs tend to remain in solution-forming complexes usually unavailable for organisms, while light REEs (such as Ce) are most likely to be assimilated by them, posing potential biological implications. In general, in seawater, the toxicity of Ce and Gd compounds may be influenced by the interaction of the metal cation (Ce 3+ or Gd 3+ ) with other conjugated anions (e.g., SO 4 2− or Cl − ) [23]. REE concentrations in the ocean generally decrease from surface waters to mid depths (ranging from 6 to 10 m), before increasing near the sea bottom [22,24], and according to Akagi et al [25], the diatoms' presence may be a major pathway of REE transport to deeper layers.…”
Section: Discussionmentioning
confidence: 99%
“…Haley et al (2014) used the term "bio-active pool" to describe the influence of biological Global Biogeochemical Cycles 10.1029/2024GB008125 processes observed in the distribution of dissolved REEs, which is attributed to bacterial activity. Sutorius et al (2022) demonstrated, by incubation experiment, that the development of phytoplanktonic and associated bacterial development significantly impacts REE distribution through sorption processes and complexation with organic matter, although this effect is only observed during bloom periods.…”
Section: Oceanmentioning
confidence: 99%
“…Sutorius et al. (2022) demonstrated, by incubation experiment, that the development of phytoplanktonic and associated bacterial development significantly impacts REE distribution through sorption processes and complexation with organic matter, although this effect is only observed during bloom periods.…”
Section: Environmental Distribution and Controlling Processes—element...mentioning
confidence: 99%
“…5). Inputs of Ln to the surface ocean are highly spatially heterogeneous including terrigenous input from rivers 39 , wind-blown dust, subaqueous volcanism and upwelling of nutrient-rich deep water 40 , while outputs canonically include precipitation, and adsorption to clay minerals 41 and planktonic biomass 42 , in addition to biological uptake as described here. We focus our discussion on three possible outputs of Ln from the surface ocean: 1.…”
Section: Marine Biogeochemistry Of the Lanthanidesmentioning
confidence: 99%